Characterization of the oxidative enzyme potential in wild white rot fungi from misiones (argentina) (2015)
This research aimed to evaluate the potential of several native white rot fungi (WRF) isolated from subtropical environments of Misiones (Argentina) to produce different ligninolytic enzymes. Coriolus versicolor f. antarcticus BAFC 266, Pycnoporus sanguineus BAFC 2126 and Phlebia brevispora BAFC 633 showed the highest phenoloxidase activity. Ganoderma applanatum strain E, P. sanguineus BAFC 2126 and P. brevispora BAFC 633 revealed marked laccase and peroxidase activity. C. versicolor f. antarcticus, G. applanatum (strain A) and Trametes villosa, gave high positive reactions with 2,6-dimethoxyphenol oxidation at the lowest tested pH. C. versicolor f. antarcticus, G. applanatum strains D and F, T. elegans BAFC 2127and T. villosa, showed the highest manganese peroxidase activity. C. versicolor f. antarcticus also produced the highest lignin peroxidase activity. Tyrosinase activity was mostly evident in G. applanatum strains (D and F) and Phanerochaete chrysosporium HHB 11741. Kraft liquor decolorization results were variable and depended on the fungus and the liquor concentration. Some fungi with moderate ligninolytic activity showed high decolorization rates (e.g. Pleurotus sajor-caju and Steccherinium sp. BAFC 1171) indicating the significance of additional approach to evaluate a potential biotechnological application. Caracterización del potencial enzimático oxidativo de cepas nativas de hongos de pudrición blanca de la selva subtropical de Misiones (Argentina)El objetivo de este trabajo fue evaluar el potencial para producir enzimas ligninolíticas de diversas cepas de hongos de pudrición blanca, nativas de la Provincia de Misiones (Argentina). Coriolus versicolor v. antarcticus BAFC 266, Pycnoporus sanguineus BAFC 2126 y Phlebia brevispora BAFC 633 mostraron un gran potencial para producir fenoloxidasas. En Ganoderma applanatum cepa E, P. sanguineus BAFC 2126  y P. brevispora BAFC 633 se observó una marcada actividad lacasa y peroxidasa. C. versicolor v. antarcticus. G. applanatum (cepa A) y Trametes  villosa, mostraron una reacción oxidativa altamente positiva sobre 2,6-dimetoxifenol a pH 4. C. versicolor v. antarcticus, G. applanatum (cepas D y F), T. elegans BAFC 2127 y T. villosa, mostraron una alta actividad manganeso peroxidasa y solo C. versicolor v. antarcticus mostró una alta actividad de lignino peroxidasa. La actividad tirosinasa fue evidente en las cepas D y F de G. applanatum y en Phanerochaete chrysosporium HHB 11741. La decoloración del licor negro Kraft reveló una actividad ligninolítica variable para las diferentes cepas estudiadas dependiendo de la concentración utilizada. Algunos hongos mostraron una moderada actividad ligninolítica con grandes halos de decoloración (p.e. Pleurotus sajor-caju y Steccherinium sp. BAFC 1171) indicando un significativo potencial para el aprovechamiento biotecnológico de estas cepas.